Selektifitas Memilih Teman dalam Tinjauan Hadis: (Studi Terhadap Pembentukan Karakter Remaja) - Erawati; Uswatun Hasanah; Sulaiman Mohammad Nur (Ta’wiluna: Jurnal Ilmu Al-Qur'an, Tafsir dan Pemikiran Islam, 2025)
Teenagers can broaden their horizons through the flow of globalization, which allows them to form friendships with individuals from different parts of the world. These friends can meet in person or virtually through social media, but the greater the involvement of both parties, the more likely it is that the relationship will lead to unexpected situations. So, it is important for teenagers to be picky in choosing friends to hang out. The goal is to prevent teenagers from engaging in deviant activities. The purpose of this research is to better understand the teachings of the hadith about choosing friends and how it relates to the development of adolescent character. This study applies a qualitative approach through literature research using ma'anil hadith studies. Some primary data sources, including hadith references on the selection of friends from the sahih bukhari hadith no. 5534 while secondary data are sourced from relevant scientific books, theses, and journals. First, the findings of this study highlight the importance of choosing the social environment carefully, because these friends greatly affect the lives of adolescents both positively and negatively. In addition to being kind, good friends can increase the teen's desire to uphold good principles, which are especially important in a religious context, as taught in Islam. Conversely, negative friends can influence teens' actions and choices. Second, it is stated in the Qur'an and the hadith of the Prophet PBUH, it is friends and companions who show the way to the truth, such as having a trustworthy leader. Like a fragrant smell comes from a perfumer and an unpleasant smell comes from a blacksmith.